Effect of Mechanical Activation in Subsequent leaching of Copper from Waste Printed Circuit Boards; MiniReview (Eurasian Research Bulletin, 2022)
The aim of this work is to determine the influence of mechanical activation in subsequent leaching of copper from waste printed circuit boards. In this mini -review, the effect of mechanical activation of subsequently copper leaching is discussed in detail based on past research efforts to provide a comprehensive image of the current status. The subsequent leaching of copper species from WPCB powder is considerably improved by mechanochemical activation. To improve copper leaching efficiency from WPCBs, mechanochemical treatment process is suggested.